Pie diabético - Echeverría G., Valentina; Sotomayor L., Camila; Norambuena G., Mackarenna; Vidal V., Pamela; Campos G., Alejandro (Revista Hospital Clínico Universidad de Chile, 2016)
The prevalence of diabetes has increased considerably, constituting a global epidemic today. Many of these patients will develop chronic complications of diabetes, including diabetic foot, which aggravates the patient’s clinical condition, decreases the quality of life and has a great socioeconomic impact. The most important action to reduce the morbidity and mortality associated with this pathology is the prevention of this complication, performing a proper metabolic management and serial control of the patient, educating about self-care of the feet. Once diabetic foot ulcer is present, the cornerstones of treatment are debridement of the wound, management of any infection, revascularization procedures when indicated, and discharge of the ulcer, all of the above in order to avoid amputation. This article intends to make a review about the epidemiology, pathophysiology, classification, diagnosis, prevention and management of diabetic foot oriented to the primary care doctor